TTF2 processes sites of incomplete DNA replication during mitosis via sister-chromatid exchanges - Ryo Fujisawa; Karim P. M. Labib (Science, 2026)
Mammalian cells frequently enter mitosis before DNA replication has finished, necessitating the rapid processing of unreplicated loci to facilitate chromosome segregation. The TRAIP ubiquitin ligase induces replisome disassembly during mitosis, triggering the cleavage of DNA replication forks. Until now, the mechanisms that regulate TRAIP and process cleaved DNA replication forks were unclear. Here we show that the TTF2 ATPase is a new type of phospho-receptor that binds a conserved phosphorylation site on TRAIP during mitosis. TTF2 couples phosphorylated TRAIP to DNA polymerase epsilon (Pol ε) in the replisome, leading TRAIP to ubiquitylate the CDC45-MCM-GINS (CMG) helicase. This triggers mitotic replisome disassembly, and a repair pathway that produces sister-chromatid exchanges, supporting a model for how fork cleavage promotes the segregation of under-replicated loci in mammalian cells.